2008
DOI: 10.1063/1.2917035
|View full text |Cite
|
Sign up to set email alerts
|

Study of D-D Reaction at the Plasma Focus Device

Abstract: Abstract. The plasma focus device PF-1000 at IPPLM Warsaw with neutron yields of 10 9 -10 11 neutrons per shot is convenient for the determination of the axial neutron energy distribution in the fusion D-D reaction due to the horizontal position of a discharge axis and the distance of scintillation detectors up to 85 m from the neutron source in both axial (downstream and upstream) directions. In this paper the determination of the axial energy component of the fast deuterons producing neutrons is presented fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It has been proved that the development of a PF discharge depends substantially on parameters of the coaxial electrodes and solid insulator as well as on the initial gas pressure [8][9][10][11][12]. The emission of intense x-ray pulses and fusion-produced neutrons (from PF discharges performed with the deuterium filling) have been investigated in details, and many efforts have concerned the optimisation of the x-ray and neutron yields [12][13][14]. Many measurements have shown that the neutron yield maximum appears at a slightly higher gas pressure than the x-ray yield peak [1,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proved that the development of a PF discharge depends substantially on parameters of the coaxial electrodes and solid insulator as well as on the initial gas pressure [8][9][10][11][12]. The emission of intense x-ray pulses and fusion-produced neutrons (from PF discharges performed with the deuterium filling) have been investigated in details, and many efforts have concerned the optimisation of the x-ray and neutron yields [12][13][14]. Many measurements have shown that the neutron yield maximum appears at a slightly higher gas pressure than the x-ray yield peak [1,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical and experimental efforts were devoted to the determination of scaling laws for the fusion-neutron production and to measurements of the basic plasma parameters, i.e. electron density and temperature [6,[14][15][16][17]. To investigate the electron density distribution the use was made of optical emission spectroscopy (OES) and laser interferometry (LI) methods.…”
Section: Introductionmentioning
confidence: 99%
“…Because of dynamo activities, current streamlines may condense into local quasi-closed formations like balls of wool with free ends, that can transport the current from the anode to the cathode even after plasma breakup. Such "balls of current streamlines" would be visible as plasma structures in VUV [18] and interferometry images [17] and be manifested as ball-like fast ion traps in reaction product images [20,21].…”
mentioning
confidence: 99%